Analysis of Victimhood in the Aceh Conflict Post the Establishment of the Aceh Truth and Reconciliation Commission - Rahmawati, Dwi; Fajar Imamudin (Universitas Islam Negeri Walisongo Semarang, 2025)
This article analyzes the armed conflict in Aceh that has left deep wounds, especially for victims who have been marginalized from the attention of law and state policy. From a victimology perspective, victims of the Aceh conflict not only experience physical and economic suffering, but also psychological and social trauma. The Aceh Peace and Reconciliation Commission (KKR Aceh) is responsible for developing a more humane approach to conflict resolution. This research uses a normative legal research method, focusing on qualitative analysis of sequential data such as laws and regulations, decision-making, and legal authority. This research method involves library research, using relevant literature, books, and documents, to provide theoretical and critical analysis. To analyzes the conditions of victims of the Aceh conflict from a victimology perspective, by highlighting the forms of physical, psychological, economic, and social suffering experienced by victims and examining the effectiveness and role of the Aceh Truth and Reconciliation Commission (KKR) in fulfilling the rights of victims of the conflict. This research is expected to contribute to the development of more humanistic legal thinking and encourage the effective implementation of transitional justice in Indonesia. Normative legal research methods, focusing on qualitative analysis of sequential data such as legislation, decision-making, and legal authority. This research method involves library research, using relevant literature, books, and documents, to provide theoretical and critical analysis. Artikel ini menganalisis tentang konflik bersenjata di Aceh telah meninggalkan penderitaan mendalam, terutama bagi para korban yang selama ini terpinggirkan dari perhatian hukum dan kebijakan negara. Dalam perspektif viktimologi, korban konflik Aceh tidak hanya mengalami penderitaan fisik dan ekonomi, tetapi juga trauma psikologis dan sosial. Komisi Perdamaian Rekonsiliasi Aceh bertanggung jawab untuk mengembangkan pendekatan penyelesaian konflik yang lebih manusiawi. Penelitian ini menerapkan metode penelitian hukum normatif, dengan memusatkan pada analisis kualitatif data berurutan sesuai perundang-undangan, pengambilan keputusan, dan kewenangan hukum. Metode penelitian ini melibatkan penelitian kepustakaan, dengan menggunakan literatur, buku, dan dokumen yang relevan, untuk memberikan analisis teoritis dan kritis. Penelitian ini menganalisis kondisi korban konflik Aceh dari perspektif viktimologi, dengan menyoroti bentuk penderitaan fisik, psikologis, ekonomi, dan sosial yang dialami korban dan menelaah efektivitas dan tugas Komisi Kebenaran Rekonsiliasi Aceh dalam memenuhi hak-hak korban konflik. Pengkajian ini diperlukan untuk kontribusi terhadap ekspansi pemikiran hukum yang lebih humanis serta mendorong implementasi keadilan transisional secara efektif di Indonesia. Aceh mengalami fase konflik bersenjata antara GAM dan pemerintah Indonesia (1976–2005), yang mengakibatkan dampak buruk bagi masyarakat, termasuk pelanggaran hak asasi manusia dan kehancuran sosial ekonomi. Hukum pidana nasional dianggap tidak efektif dalam mengatasi penderitaan korban, sehingga diperlukan pendekatan keadilan transisi melewati Komisi Kebenaran Rekonsiliasi Aceh. Keywords: Human Rights; Aceh Reconciliation Truth Commission; Victimology.